The evolution of artificial intelligence in higher education : challenges, risks, and ethical considerations - Lytras, Miltiadis D.; Alkhaldi, Afnan; Malik, Sawsan; Serban, Andreea Claudia; Aldosemani, Tahani (Emerald Publishing Limited, 2024)
Artificial Intelligence (AI) is shaping the future of higher education administration. The Evolution of Artificial Intelligence in Higher Education is a comprehensive guide to the transformative potential of AI in the higher education landscape, focused on the need to nurture technology literacy among educators and learners. Chapters explore the practicality of AI tools in academia, such as ChatGPT, and analyse the main pedagogical implications and ethical dilemmas of AI adoption in higher education, including rethinking authorship, the potential homogenisation of content, ethical implications, transparency, reliability, and bias in AI-driven processes. The Evolution of Artificial Intelligence in Higher Education presents a timely analysis of a new technological advancement with a significant impact to a diverse audience, including faculty, administrators, curriculum designers, students and policymakers who are navigating the rapidly evolving landscape of AI in education.
Keywords: Artificial intelligence -- Educational applications.; Education, Higher -- Technological innovations.; Artificial intelligence -- Moral and ethical aspects.; Education -- Computers & Technology.; Higher education, tertiary education.; Educational equipment and technology, computer-aided learning (CAL).; elektronické knihy; electronic books